Atendimento educacional especializado na perspectiva da educação inclusiva: desafios e dificuldades na escola pública - Dias, Theilon Gomes (Universidade Federal do Tocantins, 2024)
The object of this study is the specialized educational care offered in a regular school in the municipality of Miracema of Tocantins, focused on special education from the perspective of inclusive education. This research sought to understand the challenges and difficulties that teachers and other public school professionals face in the daily life of the school to work with learning difficulties, from students diagnosed with disabilities or considered with special needs. It is observed that each year increases the number of students with learning difficulties related to disabilities, global developmental disorder and other special needs that manifest themselves in the development of educational activities in schools. This fact is somewhat worrisome and provokes us reflections and concerns as educators, and nothing more than the search for knowledge, about how specialized educational care is provided to the public of special students in regular school, in accordance with Decree No. 6.571/2008 (which provides for special educational care) from the Perspective of Inclusive Education. The research allowed us to gather information in the PPP and in the secretariat of the school unit, through interviews, questionnaires, in the intention of understanding how inclusion in school happens. This paper presents a historical report of the trajectory of special education in Brazil; the legal framework of Specialized Educational Care, as well as some reflections about the training of teachers to work with special education. After all, inclusion happens with the help of all employees of the school, so in order for this to have an effect, it is necessary to focus on the work of learning by taking advantage of the skills, dispositions, willpower, interaction, finally, always respecting the limitation of the student regardless of the activities to be performed. It is evidenced by this study that inclusion can only happen in school, due to the commitment of all, because inclusive education needs financial resources, pedagogical materials, and trained professionals, and a good attentive team and with the objective of making inclusion happen according to the National Policy of the Perspective of Inclusive Education.